Effectiveness of various lower extremity rehabilitation techniques to improve quality of life in post-stroke patients - Mumtazati, Naili; Ayu Sinta, Gusti; Djajasasmita, Daswara; Taufan, Ali (ACTA Medical Health Sciences, 2024)
The ability to move the lower extremities in individuals who have suffered from a stroke presents significant challenges to daily mobility and function. We conducted a systematic evaluation to compare the effectiveness of physical rehabilitation following a stroke. We searched six databases (PubMed, Science Direct, Cochrane Library, Springer, Portal Garuda, and Nature Portfolio) for publications published before November 2023. The researchers recruited stroke patients and used a validated scale to assess lower extremity strength and walking capacity in post-stroke patients. We used the Joanna Briggs Institute Critical Appraisal Checklist to evaluate the quality of the papers that met the inclusion criteria. The PRISMA checklist was used to report the study. We identified nine relevant articles that discussed various rehabilitation methods for stroke patients with lower extremity impairment. We examined the specificity of these results using a statistical parameter. The findings were as follow: Biofeedback cycling (P < 0.001); Pelvic Stability Training (P < 0.05); Exoskeleton for post-stroke recovery of ambulation (ExStRA) (P < 0.05); Aerobic Cycling (P < 0.001); Somatosensory Training (P < 0.001), Lower-extremity constraint-induced movement therapy (P < 0.001), Motor imagery with circuit class therapy (P < 0.001), Robotic gait training (P < 0.05), and Early and Intensive  (P < 0.001). Various rehabilitation methods discussed in the article demonstrate high effectiveness in improving lower extremity function. These methods include biofeedback cycling, aerobic cycling, somatosensory training, movement therapy, motor imagery combined with structured progressive circuit therapy classes, and early and intensive rehabilitation after ischemic stroke. DOI : 10.35990/amhs.v3n2.p106-117 REFERENCES Murphy, S. J., & Werring, D. J. (2023). Stroke: Causes and clinical features. Medicine (United Kingdom), 51, 602–607. Kuriakose, D., & Xiao, Z. (2020). IMP para qué es el ictus, tipos y causas. También para datos epidemiológicos y tratamientos. International Journal of Molecular Sciences, 21, 1–24. Kuriakose, D., & Xiao, Z. (2020). Pathophysiology and treatment of stroke: Present status and future perspectives. International Journal of Molecular Sciences, 21, 1–24. Maida, C. D., et al. (2024). Molecular pathogenesis of ischemic and hemorrhagic strokes: Background and therapeutic approaches. International Journal of Molecular Sciences, 25. Medea, G. P., Nurachmah, E., & Adam, M. (2021). Post-stroke quality of life perceived by patients and caregivers. Jurnal Keperawatan Indonesia, 24, 165–172. Kwakkel, G., et al. (2023). Motor rehabilitation after stroke: European Stroke Organisation (ESO) consensus-based definition and guiding framework. European Stroke Journal, 8, 880–894. The University of North Carolina. (2016). Guide to Stroke, 1–8, 15–16. Johnson, W., Onuma, O., Owolabi, M., & Sachdev, S. (2016). Stroke: A global response is needed. Bulletin of the World Health Organization, 94, 634A–635A. Mozaffarian, D., et al. (2016). Heart disease and stroke statistics–2016 update: A report from the American Heart Association. Circulation, 133. Abdu, H., & Seyoum, G. (2022). Sex differences in stroke risk factors, clinical profiles, and in-hospital outcomes among stroke patients admitted to the medical ward of Dessie Comprehensive Specialized Hospital, Northeast Ethiopia. Degenerative Neurological and Neuromuscular Disease, 12, 133–144. Løkkegaard, E., Nielsen, L. H., & Keiding, N. (2017). Risk of stroke with various types of menopausal hormone therapies: A national cohort study. Stroke, 48, 2266–2269. Demel, S. L., Kittner, S., Ley, S. H., McDermott, M., & Rexrode, K. M. (2018). Stroke risk factors unique to women. Stroke, 49, 518–523. Bhadra, J., et al. (2021). Testosterone and estradiol in men with acute ischemic stroke: A North Indian case-control study. Current Journal of Neurology, 20, 202–207. Huang, S., et al. (2022). Research progress on the role of hormones in ischemic stroke. Frontiers in Immunology, 13, 1–15. Kementerian Kesehatan Republik Indonesia. (2018). Hasil Riset Kesehatan Dasar Tahun 2018. Mora, L., Gonzalez Alted, C., & Cocchini, G. (2023). The flubbed body: Pathological body size representation in personal neglect. Neuropsychologia, 183. Azzollini, V., Dalise, S., & Chisari, C. (2021). How does stroke affect skeletal muscle? State of the art and rehabilitation perspective. Frontiers in Neurology, 12. Desrosiers, J., et al. (2003). Comparison of changes in upper and lower extremity impairments and disabilities after stroke. International Journal of Rehabilitation Research, 26, 109–116. Li, S. (2023). Stroke recovery is a journey: Prediction and potentials of motor recovery after a stroke from a practical perspective. Life, 13, 1–13. Abdullahi, A., Wong, T. W. L., & Ng, S. S. M. (2023). Variation in the rate of recovery in motor function between the upper and lower limbs in patients with stroke. Frontiers in Neurology, 14, 1–8. Noguchi, K. S., et al. (2023). Optimal resistance exercise training parameters for stroke recovery: A protocol for a systematic review. PLOS ONE, 18, 1–10. Matozinho, C. V., et al. (2023). Relative contributions of positive, negative, and adaptive features to limitations in upper-limb function three months after stroke. Journal of Stroke and Cerebrovascular Diseases, 32. Moore, S. A., Boyne, P., Fulk, G., Verheyden, G., & Fini, N. A. (2022). Walk the Talk: Current evidence for walking recovery after stroke, future pathways and a mission for research and clinical practice. Stroke, 53, 3494–3505. Li, S., Francisco, G. E., & Zhou, P. (2018). Post-stroke hemiplegic gait: New perspective and insights. Frontiers in Physiology, 9, 1–8. Kennedy, C., et al. (2021). Factors associated with time to independent walking recovery post-stroke. Journal of Neurology, Neurosurgery & Psychiatry, 92, 702–708. Short, T., & Performance, P. A. (2014). A diagnosis of dismobility: A mobility working group recommendation. JAMA, 311, 2061–2062. Djurovic, O., et al. (2021). Risk factors related to falling in patients after stroke. Iranian Journal of Public Health, 50, 1832–1841. Tan, E., et al. (2022). The economic and health burden of stroke among younger adults in Australia: A societal perspective. BMC Public Health, 22, 1–11. Vidyanti, A. N., et al. (2022). Roles and problems of stroke caregivers: A qualitative study in Yogyakarta, Indonesia. F1000Research, 10, 1–24. Mazidah, Z., Yasin, N. M., & Kristina, S. A. (2019). Analisis biaya penyakit stroke pasien Jaminan Kesehatan Nasional di RSUD Blambangan Banyuwangi. Jurnal Manajemen dan Pelayanan Farmasi, 9, 76–87. Fadhilah, H., & Permanasari, V. Y. (2020). Economic burden bore by patients and families because of stroke: Policy assessment. Jurnal Indonesian Health Policy and Administration, 5. Gertrude, N., et al. (2019). Caring for a stroke patient: The burden and experiences of primary caregivers in Uganda – A qualitative study. Nursing Open, 6, 1551–1558. Louie, D. R., et al. (2020). Exoskeleton for post-stroke recovery of ambulation (ExStRA): Study protocol for a mixed-methods study. BMC Neurology, 20. Kim, H., Park, G., Shin, J. H., & You, J. H. (2020). Neuroplastic effects of end-effector robotic gait training for hemiparetic stroke: A randomized controlled trial. Scientific Reports, 10, 1–9. Yang, H. C., et al. (2014). Effect of biofeedback cycling training on functional recovery and walking ability of lower extremity in patients with stroke. Kaohsiung Journal of Medical Sciences, 30, 35–42. Dubey, L., Karthikbabu, S., & Mohan, D. (2018). Effects of pelvic stability training on movement control, hip muscle strength, walking speed and daily activities after stroke: A randomized controlled trial. Annals of Neurosciences, 25, 80–89. Linder, S. M., et al. (2021). Forced and voluntary aerobic cycling interventions improve walking capacity in individuals with chronic stroke. Archives of Physical Medicine and Rehabilitation, 102, 1–8. Alwhaibi, R. M., et al. (2021). Impact of somatosensory training on neural and functional recovery of lower extremity in patients with chronic stroke: A single blind controlled randomized trial. International Journal of Environmental Research and Public Health, 18. Marklund, I. et al. Lower-extremity constraint-induced movement therapy improved motor function, mobility, and walking after stroke. Eur. J. Phys. Rehabil. Med. 59, 136–144 (2023). Bovonsunthonchai, S., Aung, N., Hiengkaew, V. & Tretriluxana, J. A randomized controlled trial of motor imagery combined with structured progressive circuit class therapy on gait in stroke survivors. Sci. Rep. 10, 1–11 (2020). Wu, W. X. et al. Effect of early and intensive rehabilitation after ischemic stroke on functional recovery of the lower limbs: A pilot, randomized trial. J. Stroke Cerebrovasc. Dis. 29, (2020).